Fexofenadine Protects Against Intervertebral Disc Degeneration Through TNF Signaling - Liu, Kaiwen; Wei, Jianlu; Li, Guohua; Liu, Ronghan; Zhao, Dawang; Zhang, Yuanqiang; Shi, Jie; Xie, Qing; Cheng, Lei (Frontiers in Cell and Developmental Biology, 2021)
Objective: Fexofenadine (FFD) is an antihistamine drug with an anti-inflammatory effect. The intervertebral disc (IVD) degeneration process is involved in inflammation in which tumor necrosis factor-α (TNF-α) plays an important role. This study aims to investigate the role of FFD in the pathological process of IVD degeneration. Methods: Safranin O staining was used for the measurement of cartilageous tissue in the disc. Hematoxylin-Eosin (H&E) staining was used to determine the disc construction. A rat needle puncture model was taken advantage of to examine the role of FFD in disc degeneration in vivo. Western Blotting assay, immunochemistry, and immunoflurence staining were used for the determination of inflammatory molecules. ELISA assay was performed to detect the release of inflammatory cytokines. A real-time PCR assay was analyzed to determine the transcriptional expressions of molecules. Results: Elevated TNF-α resulted in inflammatory disc degeneration, while FFD protected against TNF-α-induced IVD degeneration. Mechanism study found FFD exhibited a disc protective effect through at least two pathways. (a) FFD inhibited TNF-α-mediated extracellular matrix (ECM) degradation and (b) FFD rescued TNF-α induced inflammation in disc degeneration. Furthermore, the present study found that FFD suppressed TNF-α mediated disc degeneration via the cPLA2/NF-κB signaling pathway. Conclusions: FFD provided another alternative for treating disc degeneration through a novel mechanism. Additionally, FFD may also be a potential target for the treatment of other inflammatory-related diseases, including IVD degeneration.